Witness discussion In light of the principles governing criminal trials: (Comparative study between the Latin system and the Anglo-American system) - .Mohamed A, Turath; .Saleem A, Rouayda; .Saleem A, Rouayda (Al-Adab Journal, 2020)
Criminal trials are characterized by the principle of confrontation in the Latin system of confronting the accused with evidence against him; thus enabling him to respond to such evidence, the accused is entitled to be present during the court's questioning of the witness of the evidence; Under the supervision of the court, the oral rule of witness testimony creates the best conditions for the conviction of the judge to present directly to the witnesses themselves. However, the written testimony may be used only with the permission of the court or the assigned judge and where this justifies the nature of the case. Due to the Code of Procedure, French law is very similar to Iraqi law with regard to fair criminal trial procedures and guarantees, and has been addressed by both the French Constitution as a primary source, and the Code of Criminal Procedure and Penalties.